2013
DOI: 10.1371/journal.pone.0058573
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Economic Inequalities in Maternal and Child Health in Urban India: A Decomposition Analysis

Abstract: Background/ObjectiveChildren and women comprise vulnerable populations in terms of health and are gravely affected by the impact of economic inequalities through multi-dimensional channels. Urban areas are believed to have better socioeconomic and maternal and child health indicators than rural areas. This perception leads to the implementation of health policies ignorant of intra-urban health inequalities. Therefore, the objective of this study is to explain the pathways of economic inequalities in maternal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 23 publications
8
57
0
Order By: Relevance
“…The results of the decomposition analysis of inequalities in child malnutrition highlight poor economic status and mother's illiteracy followed by rural areas as the major significant contributors for nutritional deficiency among children across the three rounds of NFHS. Our findings are consistent with several other studies that have shown poverty and parental education explained more than 50 and 25 percent of inequality in malnutrition, respectively (Pathak and Singh, 2011;Goli et al, 2013). Poverty is a complex phenomenon which ramifies through various channels.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the decomposition analysis of inequalities in child malnutrition highlight poor economic status and mother's illiteracy followed by rural areas as the major significant contributors for nutritional deficiency among children across the three rounds of NFHS. Our findings are consistent with several other studies that have shown poverty and parental education explained more than 50 and 25 percent of inequality in malnutrition, respectively (Pathak and Singh, 2011;Goli et al, 2013). Poverty is a complex phenomenon which ramifies through various channels.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the socioeconomic 644 IJSE 43,6 inequalities are the result of an unequal distribution of resources (Woodward and Kawachi, 2000;Wagstaff and Watanabe, 2000;Wagstaff, 2002a, b). Such avoidable inequalities are, therefore, considered as unjust (Houweling et al, 2003;Carr, 2004;Gwatkin et al, 2004) and hence, assumed as an inhibitor in achieving the Millennium Development Goals (MDGs) [2] in India, particularly MDGs one (eradicate extreme poverty and hunger), four (reduce child mortality) and five (improve maternal health) (Subramanian and Smith, 2006;Mohanty and Pathak, 2009;Goli et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of illiteracy and poverty to inequality in institutional deliveries were reported by an Indian study conducted prior to the JSY, though this study reported an effect of literacy among women and men (Goli et al, 2013). Experience from neighbouring Bangladesh also suggest that although a demand side financing program raised the utilization of maternal health services in poor population groups, a pro-rich slant in utilization persisted which indicates that a demand-side financing program alone is not a sufficient measure (Ahmed and Khan, 2011).…”
Section: Inequality In Institutional Deliveries and Emocmentioning
confidence: 72%
“…Illiteracy was the key predictor for a number of antenatal care check-ups, institutional delivery, child immunization and infant deaths while low socioeconomic status was the key predictor for underweight children. This study shows a relationship between socioeconomic status and access to and utilization of care in urban populations in India (Goli, Doshi & Perianayagam, 2013).…”
Section: Hiv/aidsmentioning
confidence: 71%